Fully percutaneous fetoscopic repair of myelomeningocele: 30‐month follow‐up data. (2nd January 2021) - Diehl, D.; Belke, F.; Kohl, T.; Axt‐Fliedner, R.; Degenhardt, J.; Khaleeva, A.; Oehmke, F.; Faas, D.; Ehrhardt, H.; Kolodziej, M.; Uhl, E.; Windhorst, A. C.; et al.
ABSTRACT: Objective: This observational study reports on the postnatal mortality and 30‐month outcome of children who underwent fully percutaneous fetoscopic repair of myelomeningocele (MMC) at a single center in Giessen, Germany. Methods: Between October 2010 and August 2014, a total of 72 patients underwent fully percutaneous fetoscopic MMC closure at 21 + 0 to 29 + 1 (mean, 23 + 5) weeks' gestation. Of these, 52 (72%) participated in this study; however, 30‐month mortality data are available for all 72 children. Children were examined at four timepoints: shortly after birth and at 3 months, 12 months and 30 months of corrected age. The patients underwent age‐specific standardized neurological examinations and assessment of leg movements and ambulation at all timepoints. Cognitive and motor development were assessed using the Bayley Scales of Infant Development, second edition (BSID‐II), at 30 months. Results: All 72 children survived the intrauterine procedure, however, four (5.6%) infants died postnatally (including two of the 52 comprising the study cohort). Of the 52 patients included in the study, 11.5% were delivered before the 30 th week of gestation (mean, 33 + 1 weeks) and, of the survivors, 48.1% had ventriculoperitoneal shunt placement. Of the 50 infants that were alive at 30 months, independent ambulation, without orthosis, was feasible for 46%. At 30 months of follow‐up, 46% of children presented with a functional level that was at least two segments better than the anatomical level of the lesion. At 30 months, 70% of the children presented with BSID‐II psychomotor development index score of ≥ 70 and 80% with BSID‐II mental development index score of ≥ 70. Conclusion: Intrauterine repair of MMC by percutaneous fetoscopy shows largely similar outcomes to those reported for open repair, with respect to mortality, prematurity, shunt‐placement rates, motor and mental development and free ambulation. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.